The stress-strain state of the trailer seat-coupling device simulation - Shalupina P.I.; Ragulina Yu.V. (Научно-технический вестник Брянского государственного университета)
The article deals with the issues of modeling the stress-strain state of a traction device designed for towing a heavy semi-trailer, on which the equipment of the base station of a mobile transport and reloading rope complex is placed. The main design loads are defined. Geometric and computational finite element models are constructed, taking into account the features of the metal structure. The method of gluing elements of the grid model is applied. On the basis of the performed calculations, conclusions are drawn about the compliance of the developed structure with the requirements of strength.